Wrench perception in intermediary telepresence for remote manipulation. Issue 3 (18th May 2015) - Shirwalkar, Varsha; Dwarakanath, T.A.; Bhutani, Gaurav
Abstract : Purpose: The purpose of this paper is to conduct a reliable remote manipulation with good contact perception of the remote site. The long-term experience of the authors' repeatedly confirm that the highest relevance lies in monitoring the wrench acting at a structurally weak point of the work piece rather than monitoring the wrench experienced by the robot end-effector. Design/methodology/approach: The approach followed here is to sense the wrench at the interface of the robot end-effector and the environment. Position and orientation data and environment model are used to arrive at the contact point in real time. The intent of remote contact procedure is understood based on the knowledge of motion trajectory. All the above information is used to develop a wrench transformation to obtain the force diagrams. Findings: The haptic solutions greatly suffer from objectivity, and therefore may result in inconsistency in an operator's role. Intermediary telepresence through the visual communication of the wrench at the remote site in the form of force diagram provides excellent consistency across the operators and operations. Observing six components of the wrench in separate graphs does not provide on-line error estimate. Force diagrams suggested in the paper are found to be highly effective in perceiving the wrench. Practical implications: The contact mode operations like assembly, surgery, docking, etc. still suffer due to the lack of easily perceivable wrench visualization. This paper provides solution to such practical issues. Originality/value: The concept is original, and has evolved steadily over a period of time.